Cancer, obesity and immunometabolism – Connecting the dots. (28th March 2018) - Dyck, Lydia; Lynch, Lydia
Highlights: Lipid metabolism plays a key role in the tumour microenvironment. Lipid metabolism in both the tumour and immune cells can promote tumour progression. Obesity is associated with impaired immune surveillance. Lipid metabolism may link obesity and increased cancer risk.